SYNERGISTIC EFFECTS OF URSOLIC ACID COMPLEXES WITH COPPER, SELENIUM, AND ZINC: A NOVEL APPROACH TO RHEUMATOID ARTHRITIS MANAGEMENT - Farhana Ayub; Abdul Khaliq Naveed; Adnan Jehangir (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study aims to investigate novel compounds that join together trace elements copper (Cu) and selenium (Se) both in the presence of the known bioactive compound, ursolic acid (UA), applied with buffered zinc chloride for anti-inflammation and immunomodulation. The study uses Freund’s complete adjuvant (FCA) such as an arthritic rat model to assess the ameliorative role of UA+Cu, UA+Se, and UA+Zn against both individual elements and lornoxicam (LX), the drug of choice. Using reverse transcriptase polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA), the results show that UA complexes markedly reduced pro-inflammatory cytokines of TNF-α and NFκB, whilst upregulated anti-inflammatory markers of IL-4 and IL-10. Moreover, UA combinations significantly decreased levels of serum nitric oxide (NO), cyclooxygenase-2 (COX-2), and lipoxygenase (LOX). In contrast, UA complexes showed no evidence for nephrotoxic or hepatotoxic effects presenting a safe treatment option against RA compared to standard therapies. The synthetic efficacy of UA with trace elements TE in a retarding RA sign is revealed ever based on the current study. It may have scientific guidance for future clinical translation.